Structural behaviour of concrete-encased CFST box stub columns under axial compression. (July 2019) - Chen, Jin-Yang; Li, Wei; Han, Lin-Hai; Wang, Fa-Cheng; Mu, Ting-Min
Abstract: The axial performance of a type of concrete-encased CFST box stub column, which consists of the outer reinforced concrete (RC) box column and six embedded CFST components, is investigated in this study. A total of eight axial compression tests on the concrete-encased CSFT box specimens under axial compression were carried out. A finite element analysis (FEA) model was developed to analyze the structural behavior of the composite columns. The effects of material nonlinearity and interaction properties between the concrete and the steel tubes on the simulation were considered. The verified FEA model was then used to conduct a full-range analysis on the load-deformation responses. The results of typical failure modes, internal load and stress distributions and the contact stresses between the concrete and the steel tubes were also discussed. Parametric studies were conducted to investigate the effects of geometric and material properties on the compressive behavior of the concrete-encased CSFT box members. Finally, a simplified model was proposed to predict the ultimate strength and the initial stiffness of the concrete-encased CFST box stub columns under axial compression. Highlights: Concrete-encased CFST box columns are tested under axial compression. An FEA model is developed to represent the concrete-encased CFST box column. Full-range analysis of the composite column is investigated. Parametric studies are conducted to investigate the influences of various parameters. Simplified model is suggested to predict the ultimate strength.